The experience-dependent increase in deep sleep activity is reduced in children with attention-deficit/hyperactivity disorder - Furrer, Melanie; Ringli, Maya; Kurth, Salome; Brandeis, Daniel; Jenni, Oskar; Huber, Reto (Sleep medicine, 2020)
Objective/Background - Learning of a visuomotor adaptation task during wakefulness leads to a local increase in slow-wave activity (SWA, EEG power between 1 and 4.5 Hz) during subsequent deep sleep. Here, we examined this relationship between learning and SWA in children with attention-deficit/hyperactivity disorder (ADHD). - Patients/Methods - Participants were 15 children with ADHD (9.7-14.8 y, one female) and 15 age-matched healthy controls (9.6-15.7 y, three female). After the completion of a visuomotor adaptation task in the evening, participants underwent an all-night high-density (HD, 128 electrodes) sleep-EEG measurement. - Results - Healthy control children showed the expected right-parietal increase in sleep SWA after visuomotor learning. Despite no difference in visuomotor learning, the local up-regulation during sleep was significantly reduced in ADHD patients compared to healthy controls. - Conclusions - Our results indicate that the local, experience-dependent regulation of SWA is different in ADHD patients. Because the customarily observed heightened regulation in children was related to sensitive period maturation, ADHD patients may lack certain sensitive periods or show a developmental delay.